2014
DOI: 10.1182/blood-2013-12-543074
|View full text |Cite
|
Sign up to set email alerts
|

GpIbα-VWF blockade restores vessel patency by dissolving platelet aggregates formed under very high shear rate in mice

Abstract: Key Points• Following endothelial damage, platelet cross-linking during closure of the vessel lumen is mediated by GpIba-VWF interactions.• Disruption of GpIba-VWF interactions restores vessel patency by specifically disaggregating the external layer of occlusive thrombi.Interactions between platelet glycoprotein (Gp) IIb/IIIa and plasma proteins mediate platelet cross-linking in arterial thrombi. However, GpIIb/IIIa inhibitors fail to disperse platelet aggregates after myocardial infarction or ischemic stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 38 publications
5
55
0
1
Order By: Relevance
“…A combination of both strategies could even further improve thrombolytic success. 38 A promising aspect of this approach, at least in experimental models, is the absence of bleeding, in contrast to t-PA. 34,38,39 We did not observe any bleeding complications when treating mice with rhADAMTS13, which is in line with previous studies on the safe use of ADAMTS13 in stroke experiments. 21 ADAMTS13 even reduced bleeding complications associated with t-PA in another murine stroke model.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A combination of both strategies could even further improve thrombolytic success. 38 A promising aspect of this approach, at least in experimental models, is the absence of bleeding, in contrast to t-PA. 34,38,39 We did not observe any bleeding complications when treating mice with rhADAMTS13, which is in line with previous studies on the safe use of ADAMTS13 in stroke experiments. 21 ADAMTS13 even reduced bleeding complications associated with t-PA in another murine stroke model.…”
Section: Discussionsupporting
confidence: 89%
“…38,39 Thus, targeting VWF either via direct cleavage by ADAMTS13 or by inhibition of VWF-platelet binding might become an interesting alternative strategy in thrombolytic therapy. A combination of both strategies could even further improve thrombolytic success.…”
Section: Discussionmentioning
confidence: 99%
“…This absence of restoration of Wistar rat vessel patency is consistent with a hierarchical process of occlusive thrombosis in which platelet-platelet cross-linking in the inner core mainly involves GPIIb/IIIa, whereas once the thrombus has occluded 50% of the artery, platelet cross-linking in the external layer occurs in a GPIbα-vWF-dependent manner. 32,33 Although it is now increasingly recognized that multiple concomitant mechanisms regulate the formation and stability of arterial thrombi, our study further points to the attractiveness of this GPIbα-vWF axis as a potential therapeutic target for occlusive thrombosis in the context of hypertension. Whether coadministration of an inhibitor of GPIbα-vWF interactions and a specific inhibitor of integrin α v β 3 to target thrombin generation on the surface of SMCs may lead to the development of more efficient therapeutic strategies remains to be investigated.…”
Section: Discussionmentioning
confidence: 70%
“…Recent data have highlighted the role of GPIbα-vWF interactions during vessel lumen closure and revealed that disruption of these interactions restores vessel patency after occlusive thrombosis but with a limited therapeutic window. 32 Whereas fully occlusive thrombi in SHR were efficiently disaggregated by GPIbα-vWF inhibitors, nonocclusive thrombi in Wistar rats were resistant. This absence of restoration of Wistar rat vessel patency is consistent with a hierarchical process of occlusive thrombosis in which platelet-platelet cross-linking in the inner core mainly involves GPIIb/IIIa, whereas once the thrombus has occluded 50% of the artery, platelet cross-linking in the external layer occurs in a GPIbα-vWF-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that NAC promotes disaggregation of arterial thrombi by interfering with the platelet/VWF interactions and interfering with disulfide bonds inside multimeric VWF 8,9 . To investigate if NAC had a similar effect during the formation of stagnation point thrombi, the assay was repeated with a high dose of NAC.…”
Section: Resultsmentioning
confidence: 99%